Dynamics of Social Activity and Intelligence in Young People: Problems and Solutions - Usmanova Shoira Djumabekovna (Zien Journals, 2022)
Analysis and dynamics intellect of student’s Usmаnova Shoira Jumabekovna. As a result, students' intelligence in psychology has increased. It was discovered through a process of investigating the social-psychological quality of a dynamic's development, maintenance of its organization, ways, forms, and methods, as well as elaborated theoretical approaches, problem-solving hypotheses, conceptions, and scientific-methodical recommendations. These methods can be applied to the development of work sections and young organizations, textbook content determination, and educational-methodical work in higher education institutions
Keywords: Intellect; sensible skills; social and emotionalintellect; ability for empathy